Numerical experiments on the PF1000 plasma focus device operated with nitrogen and oxygen gases - Akel, M.; Ismael, Sh.; Lee, S.; Saw, S. H.; Kunze, H. J. (World Scientific Publishing Co Pte Ltd, 2017)
The indicative values of reduced Pease–Braginskii (P–B) currents are estimated for a nitrogen and oxygen plasma focus. The values of depletion times indicate that in N2 and O2 with estimated 3–4% of pinch energy radiating away over the duration of the pinch, we may expect some cooling effects leading to small reductions in radius ratio. In other gases with higher atomic number, the pinch duration is much more than the depletion time, so radiative contraction may be anticipated. The Lee model was employed to study the soft X-ray from PF1000 operated with nitrogen and oxygen. We found nitrogen soft X-ray yield in the water window region of 3.13 kJ, with the corresponding efficiency of 0.9% of the stored energy (E0)(E0), while for the oxygen it was found to be YsxrYsxr = 4.9 kJ, with the efficiency of 1.4% E0E0. The very modest enhancement of compression (radius ratios around 0.1) in the pinches of these two gases gives rise to rather modest pinch energy densities (PEDs) under 109 Jm−3−3. This is in contrast to Kr or Xe where it had been shown that the radiative collapse leads to radius ratios of 0.007 and 0.003, respectively, with PEDs going to large values considerably exceeding 101212 Jm−3−3.